Applying configurational theory to build a typology of ethnocentric consumers - Feurer, S.; Baumbach, E.; Woodside, Arch (MCB University Press, 2016)
Purpose – Individuals showing high consumer ethnocentrism (CE) prefer domestic over foreign-made products and their preferences may contribute to barriers to international market entry. Therefore, how to identify such consumers is an important question. Shankarmahesh’s (2006) review reveals inconsistencies in the literature with regard to CE and its antecedents. To shed theoretical and empirical light on these inconsistencies, the purpose of this paper is to contribute two new perspectives on CE: first, a typology that classifies ethnocentric consumers by the extent to which they support government-controlled protectionism and consumer-controlled protectionism; and second, a configurational (recipe) perspective on the antecedents. Design/methodology/approach – The study applies fuzzy-set qualitative comparative analysis of survey data from 3,859 consumers. The study contrasts the findings with findings using traditional statistical hypotheses testing via multiple regression analysis. Findings – The results reveal several configurations of antecedents that are sufficient for consistently explaining three distinct types of CE. No single antecedent condition is necessary for high CE to occur. Practical implications – The findings help global business strategists in their market entry decisions and in their targeting and segmentation efforts. Originality/value – The authors show the value of asymmetrical thinking about the relationship between CE and its antecedents. The results expand understanding of CE and challenge conventional net-effects thinking about its antecedents.